Cancer antigen-125 levels predict long-term mortality in chronic obstructive pulmonary disease. (March 2015) - Kaya, Hakki; Zorlu, Ali; Yucel, Hasan; Dogan, Omer Tamer; Sarikaya, Savas; Aydin, Gulay; Kivrak, Tarik; Yilmaz, Mehmet Birhan
Abstract Background: Cancer antigen-125 (CA-125) might be a useful biomarker to predict long-term mortality in patients with recent exacerbation of chronic obstructive pulmonary disease (COPD). Methods: A total of 87 consecutive patients with COPD were evaluated prospectively. Mean age of patients was 68 ± 10 years (55% males, 45% females) with a median follow-up period of 49 months. Optimal cut-off value of CA-125 to predict mortality was found as >93.34 U/ml, with 91% specificity and 40% sensitivity. Results: After follow-up, 20 out of 87 (23%) experienced cardiovascular death. CA-125 levels were higher among those who died compared to those who survived [55 (12–264) versus 28 (5–245) U/ml, p = 0.013]. In multivariate Cox proportional-hazards model with forward stepwise method, only CA-125 > 93.34 U/ml on admission (HR = 3.713, 95% CI: 1.035–13.323, p = 0.044) remained associated with an increased risk of death. Conclusions: For the first time, we demonstrated that CA-125 helps the risk stratification of patients with COPD.